Report on the state of the European Union - Padoa-Schioppa, Fiorella, 1945- (Palgrave Macmillan, 2005)
This yearly report aims to examine and monitor process of European integration, and analyses the growing role played by EU institutions (Parliament, Council, Commission, Court of Justice) in shaping - through several legislative instruments - the rules governing an increasing number of sectors of the European economy. Itt is a rigorous, albeit non-technical, analysis of a wide range of topics, from the Euro takeoff to competition policy, from the diffusion of the principle of mutual recognition to the consequences of the EU "enlargement" towards Central-Eastern Europe. The report is written in an accessible way focusing on different topics each year depending upon their relevance and current importance. It will be a useful resource for academics and policymakers, journalists, and government advisors